2005
DOI: 10.1161/01.str.0000190004.36793.2d
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Oxidase and Acrolein as Novel Biochemical Markers for Diagnosis of Cerebral Stroke

Abstract: Background and Purpose-We found previously that plasma levels of acrolein (CH 2 ϭCHCHO) and spermine oxidase (SMO) were well correlated with the degree of severity of chronic renal failure. The aim of this study was to test whether the levels of these 2 markers and of acetylpolyamine oxidase (AcPAO) were increased in the plasma of stroke patients. Methods-The activity of AcPAO and SMO and the level of protein-conjugated acrolein in plasma of the stroke patients and normal subjects were measured by high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 19 publications
5
111
0
Order By: Relevance
“…We recently found that increased levels of protein-conjugated acrolein (PC-Acro) and the enzymes responsible for its production, polyamine oxidases (spermine oxidase and acetylpolyamine oxidase), are good biomarkers for human stroke. 1 We also found that measurement of PC-Acro together with interleukin-6 and C-reactive protein makes it possible to identify small infarctions, that is, silent brain infarction, with high sensitivity (89%) and specificity (91%). 2 This tool for early identification of stroke may help in the application of suitable therapy to delay or reduce aggravation of stroke.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…We recently found that increased levels of protein-conjugated acrolein (PC-Acro) and the enzymes responsible for its production, polyamine oxidases (spermine oxidase and acetylpolyamine oxidase), are good biomarkers for human stroke. 1 We also found that measurement of PC-Acro together with interleukin-6 and C-reactive protein makes it possible to identify small infarctions, that is, silent brain infarction, with high sensitivity (89%) and specificity (91%). 2 This tool for early identification of stroke may help in the application of suitable therapy to delay or reduce aggravation of stroke.…”
mentioning
confidence: 69%
“…Accordingly, severity of renal failure and cerebral stroke is correlated well with the level of protein-conjugated acrolein. 1,2,18,30 …”
mentioning
confidence: 99%
“…In addition to H 2 O 2 , SMO produces 3-aminopropanal, a byproduct that contributes to the formation of acrolein, a highly reactive aldehyde. Acrolein associated with elevated polyamine catabolism has been strongly implicated in the etiology of diseases including ischemia-reperfusion injuries, renal failure, stroke, and silent brain infarction (39)(40)(41)(42)(43)(44). Further, elevated SMO expression has been observed in inflammation-associated human diseases including gastritis (22), ulcerative colitis (23), and prostatic intraepithelial neoplasia (24).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, elevated levels of an acrolein-protein conjugate ( N ⑀ -(3-formyl-3,4-dehydropiperidino)-lysine, FDP-lysine) 61 , 69 were demonstrated in plasma of stroke patients using ACR-Lysine Adduct ELISA System (NOF Corporation, Tokyo, Japan). 70 In addition to its formation as a lipid peroxidation byproduct, acrolein is a ubiquitous environmental contaminant that is present in automobile exhaust and formed by the burning of fats during cooking. 71 Acrolein, by far the strongest electrophile among all ␣ , ␤ -unsaturated aldehydes, reacts with DNA bases including guanine, adenine, cytosine, and thymidine to form cyclic adducts, the major exocyclic adduct being acrolein-deoxyguanosine.…”
mentioning
confidence: 99%